A meta-analysis of program for the reduction of physical restraint use in intensive care units in China (国内ICU患者缩减身体约束行动实施效果的Meta分析) - CHEN Zetao (陈泽涛); LI Xiaobing (李晓彬); SHI Yu (石宇); ZHANG Yanfei (张雁飞); YANG Wencai (杨文才); SHAN Miaohang (单妙航) (中西医结合护理)
Objective This study aimed to evaluate the effectiveness of implementing program for the reduction of physical restraint use in intensive care unit (ICU) patients within China. Methods A computer-assisted search was conducted for randomized controlled trials on the practice of reduced physical restraint actions in the China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, and the Chinese BioMedical Literature Database (CBM). The search period spanned from the inception of the databases to June 2024. Two researchers independently screened literature, extracted data, assessed the risk of bias, and performed statistical analysis using RevMan 5. 4 software. Results A total of 13 articles were included, covering 3209 ICU patients. Meta-analysis results indicated that the implementation of reduced physical restraint actions effectively reduced the rate of physical restraint use ［OR=2. 17, 95% CI(1. 86, 2. 53), P＜0. 01］, shortened the average duration of physical restraint ［MD=18. 81, 95% CI(10. 32, 27. 29), P＜0. 01］, decreased the incidence of unplanned extubation ［OR=2. 42, 95% CI(1. 65, 3. 56), P＜0. 01］, and reduced the incidence of restraint-related complications ［OR=3. 76, 95% CI(2. 78, 5. 09), P＜0. 01］. Subgroup analysis results showed that collaboration between medical and nursing staff could further reduce the rate of physical restraint use (χ²=13. 989, P＜0. 01). Conclusion The implementation of reduced physical restraint actions in Chinese ICUs has effectively reduced the rate of physical restraint use, shortened the average duration of restraint, and decreased the incidence of unplanned extubation and restraint-related complications. The collaboration of multidisciplinary teams has shown even more significant effects, which warrants further promotion and optimization in clinical practice. (目的 评价国内ICU患者缩减身体约束的实施效果。方法 计算机检索中国知网(CNKI)、万方数据库、维普数据库(VIP)、中国生物医学文献数据库(CBM)中关于缩减身体约束行动实践的随机对照试验, 检索时限为建库至2024年6月。由两名研究者独立筛选文献、提取资料、评价偏倚风险, 使用RevMan 5. 4软件进行统计分析。结果 共纳入文献13篇, 涵盖3209名ICU患者, Meta分析结果显示, 缩减身体约束行动能有效降低身体约束使用率［OR=2. 17, 95%CI(1. 86, 2. 53), P＜0. 01］、缩短身体约束平均时长［MD=18. 81, 95%CI(10. 32, 27. 29), P＜0. 01］、降低非计划拔管发生率［OR=2. 42, 95%CI(1. 65, 3. 56), P＜0. 01］及约束相关并发症发生率［OR=3. 76, 95%CI(2. 78, 5. 09), P＜0. 01］。亚组分析结果显示, 医护合作能进一步降低身体约束使用率(χ²=13. 989, P＜0. 01)。结论 国内ICU对缩减身体约束行动的落实, 能有效降低身体约束使用率、缩短身体约束平均时长、降低非计划拔管及约束相关并发症发生率, 多学科团队协作效果更为显著, 值得临床实践进一步推广和优化。)